Mortality due to malformations of the circulatory system in children under 1 year of age in the Southeast region of Brazil between 2014 and 2019 (Research, Society and Development, 2022)
Objective: To analyze the mortality rates due to congenital malformations in the circulatory system in children younger than 1 year in the Southeast region of Brazil between 2014 and 2019. Methods: This is an ecological time series study carried out through the quantitative and qualitative analysis of the sample composed of deaths of children under 1 year old, as a result of congenital malformations in the circulatory system, in the Southeast region of Brazil in the period between 2014 and 2019. Data were collected from the Mortality Information System (SIM), made available through the Informatics Department of the Unified Health System (DATASUS). All notifications made during the six-year period studied were included and information not computed by the SIM was excluded. The analysis of epidemiological aspects was based on the following variables: year of death, Federation Unit (UF), place of occurrence, color/race and sex. Results: A total of 9,884 deaths were computed, distributed with little variation between the years observed. Of these, 51.82% occurred in the state of São Paulo; 94.55% in a hospital environment; 62.09% in children of color/white race and 53.3% in male children. Conclusion: The present study elucidated and related the epidemiological aspects of deaths from congenital malformations in the circulatory system in children under 1 year of age between 2014 and 2019, thus contributing to the recognition of the impact of these conditions on the child's life and the importance of early diagnostic measures in reducing mortality.